Identifying diagnostic markers and constructing a prognostic model for small-cell lung cancer based on blood exosome-related genes and machine-learning methods - Zhang, Kun; Zhang, Chaoguo; Wang, Ke; Teng, Xiuli; Chen, Mingwei (Frontiers in Oncology, 2022)
Background: Small-cell lung cancer (SCLC) usually presents as an extensive disease with an extremely poor prognosis at the time of diagnosis. Exosomes are rich in biological information and have a powerful impact on tumor progression and metastasis. Therefore, this study aimed to screen for diagnostic markers of blood exosomes in SCLC patients and to build a prognostic model. Methods: We identified blood exosome differentially expressed (DE) RNAs in the exoRBase cohort and identified feature RNAs by LASSO, Random Forest, and SVM-REF three algorithms. Then, we identified DE genes (DEGs) between SCLC tissues and normal lung tissues in the GEO cohort and obtained exosome-associated DEGs (EDEGs) by intersection with exosomal DEmRNAs. Finally, we performed univariate Cox, LASSO, and multivariate Cox regression analysis on EDEGs to construct the model. We then compared the patients' overall survival (OS) between two risk groups and assessed the independent prognostic value of the model using receiver operating characteristic (ROC) curve analysis. Results: We identified 952 DEmRNAs, 210 DElncRNAs, and 190 DEcircRNAs of exosomes and identified 13 feature RNAs with good diagnostic value. Then, we obtained 274 EDEGs and constructed a risk model containing 7 genes (TBX21, ZFHX2, HIST2H2BE, LTBP1, SIAE, HIST1H2AL, and TSPAN9). The low-risk patients had a longer OS time than the high-risk patients. The risk model can independently predict the prognosis of SCLC patients with the areas under the ROC curve (AUC) at 1 year of 0.820, 3 years of 0.952, and 5 years of 0.989. Conclusions: We identified 13 valuable diagnostic markers in the exosomes of SCLC patients and constructed a new promising prognostic model for SCLC.